Bacterial inoculations can perturb the growth trajectory of diatoms with an existing microbiome - Baker, Lydia J.; Kemp, Paul F. (PeerJ, 2020)
Inoculation of axenic diatom monocultures with individual bacterial strains has been used effectively to examine the relationship between bacteria and a diatom host. Both beneficial and harmful effects on diatom fitness have been observed. Yet, diatoms commonly host a consortium of bacteria that could influence their response to perturbation by bacterial inoculations. In this study, diatom cultures with an existing microbiome were inoculated with individual bacterial strains. Strains of two genera of bacteria commonly found associated with diatoms (Alteromonas and Marinobacter) were isolated from a culture of the diatom Chaetoceros sp. KBDT20. To evaluate whether bacterial inoculations can impact the growth, peak abundance, or decline of diatoms with an intact microbiome, individual bacterial strains were inoculated into batch cultures of the original host as well as two non-origin diatom hosts (Chaetoceros sp. KBDT32 and Amphiprora sp. KBDT35). Inoculations were repeated under vitamin-replete and vitamin-deficient conditions to assess whether vitamin concentration modulates the impact of bacterial inoculations on the host. The origin Chaetoceros culture was largely unperturbed by bacterial inoculations. In contrast, non-origin hosts experienced long-term impacts on their growth trajectory, and those impacts were found to be dependent on the concentration of vitamins in the growth medium. For the non-origin Chaetoceros, all positive impacts were observed in vitamin-replete conditions and all negative impacts were observed in vitamin-deficient conditions. Amphiprora was only impacted by inoculation with Marinobacter strains in vitamin-deficient conditions, and the effect was negative. Neither individual bacterial strains nor genera resulted in exclusively beneficial nor detrimental impacts, and the magnitude of effect varied among bacterial strains. This study demonstrates that bacterial inoculations can have long-lasting impacts on the growth trajectory of diatoms with an existing microbiome, that this impact can differ even between congeneric diatoms, and that the impact can be significantly modulated by vitamin concentration.
Keywords: Algal-bacterial interaction; Symbiosis; Microbiome; Xenic; Marine diatom